Combination of a v-grooved solar collector with a single slope solar still: Performance evaluation, mathematical modeling, and economic analysis. (August 2022) - Azari, Parisa; Mirabdolah Lavasani, Arash; Rahbar, Nader; Eftekhari Yazdi, Mohammad
Solar stills are known as one of the best and most efficient methods for water desalination. Due to low production of solar stills, researchers have been using experimental and theoretical methods to come up with possible solutions for ameliorating freshwater production through these systems. This study aims to investigate the performance of a single slope solar still combined with a v-grooved solar air heater. Important parameters (height of the v-grooves, length of the collector, and air mass flow) affecting the performance of the proposed system were mathematically investigated using MATLAB software. The average deviation between the experimental and theoretical results was found to be about 7%. Furthermore, the results showed that the water production rate and the efficiency of the modified solar still were 150% and 44.20% higher than those of the conventional ones, respectively. Two new correlations were proposed based on the experimental results in order to predict the water production via solar stills, which are in good agreement with the results of the existing models. Based on the obtained results, the increase in the inlet air mass flow rate was not conducive to water production as the production rate was reduced by 60%. In addition, through the economic analysis, the cost per liter for the modified still was determined to be 0.03( $ /L/m 2 ) with an interest rate of 10%.